Effect of Mulch and Strengthened Terrace Strips on Erosion, Sediment Enrichment Ratio, and Nutrient Loss Through Erosion - Suyana, Jaka; Nugraheni, Nugraheni (UNIVERSITY OF LAMPUNG, 2022)
Mulching technology is accessible to farmers and can also reduce soil erosion and nutrient loss through erosion. This research aimed to observe the effectiveness of the combination treatment of strengthened terrace strips and maize stalk mulch on runoff, erosion, sediment enrichment ratio (SER), and nutrient loss through erosion. The experiment was conducted on upland farming on Andisol at the end of the rainy season. The erosion plot experiment was arranged in a Randomized Block Design (RBD) with the treatment of 4 doses of maize stalks mulch (0, 4, 8, and 12 Mg ha-1) and three types of strengthened terrace strips (Jali, Vetiver, and Kalanjana grass) put in groups/blocks, giving 12 experiments. The combination treatment of maize stalk mulch and strengthened terrace strips has not significantly reduced runoff and soil loss. The treatment mulch dose of 12 MgÂ ha-1 reduced runoff and soil loss by 9.9% and 21.9% compared to without mulch. The application of maize stalks mulch tends to reduce the sediment concentration and the number of nutrients (N and Organic C) lost through erosion but increases the nutrient concentration in sediments (SER value).